Cemaran Mikrobiologi Pada Tepung Karagenan - Salawati, Abraham Imanuel; Montolalu, Roike Iwan; Damongilala, Lena Jeane; Reo, Albert Royke; Wonggo, Djuhria; Makapedua, Daisy Monica; Sanger, Grace (Sam Ratulangi University, 2021)
The purpose of this study was to examine the microbiological contamination of carrageenan flour made by the steam method. In this study raw seaweed was used with 0.1%, 0.2%, 0.3% NaOH, and drying time. The results of this study obtained the highest yield at the concentration of NaOH 0.3% for 8 hours drying of the Sun that is equal to 19.48%. The lowest water content at the NaOH concentration of 0.3% increases in the drying time of the 12-hour drying cabinet which is 3.7%. Frequency pH stability 8.44 - 9.7. Research Results in The best total Plate Figures at a concentration of NaOH 0.3% for 8 hours of Sun Drying is 3000 colonies / g. The results of the study of Escherichia coli, Salmonella sp. Get negative results.Tujuan dari penelitian ini untuk mengetahui cemaran mikrobiologis pada tepung karagenan yang dibuat dengan metode uap. Pada penelitian ini digunakan perlakuan bahan baku rumput laut dengan dengan pelarut NaOH 0.1%, 0.2%, 0.3% dan lama pengeringan. Hasil penelitian ini diperoleh rendemen terbanyak pada konsentrasi NaOH 0.3% lama Pengeringan Matahari 8 jam yaitu sebesar 19.48%. Kadar air terendah pada konsentrasi NaOH 0.3% lama pengeringan Pengeringan Cabinet dryer 12 jam yaitu sebesar 3.7%. Stabilitas pH berkisar 8.44 â€“ 9.7. Hasil Penelitian Angka Lempeng Total terbaik pada konsentrasi NaOH 0.3% dengan lama Pengeringan Matahari 8 jam yaitu sebesar 3000 koloni/g. Hasil penelitian Escherichia coli, Salmonella sp diperoleh hasil negatif.Â Â